O uso de plantas medicinais na comunidade quilombola de São Benedito da Ponta, Ilha do Marajó/PA - SANTOS, Fabíola Oliveira (2023)
This work, in the form of an action plan, aims to produce didactic material regarding the use of medicinal plants in the Quilombola Community of São Benedito da Ponta, Ilha do Marajó-PA. The work seeks to value and pass on traditional knowledge related to medicinal plants to the new generations of the community. For the development of didactic material, the methodology used was research and the ethnographic method, based on interviews with community members, especially women, participant observation and pedagogical workshops. From the research, it was possible to observe that due to the precariousness of health services in the community, traditional knowledge related to the use of medicinal plants is used to combat various diseases, such as flu, diarrhea, blood pressure, diabetes, etc. However, the new generations do not show interest in learning how to use medicinal plants and prefer to use medicines of pharmaceutical origin.